Two new Neotropical spiders of the genera Oecobius and Platoecobius (Araneae: Oecobiidae) - Santos, Adalberto J.; Gonzaga, Marcelo O. (Zootaxa, 2008)
Two new species of Oecobiidae are described from Central and South America, representing the first native members of the family recorded south of Mexico. Oecobius eberhardi sp.nov. is described based on male and female specimens collected from two localities in Costa Rica. Platoecobius kooch sp.nov., the second species in the genus, is described from female specimens collected in Southern Argentina. A new diagnosis is proposed for the genus Platoecobius Chamberlin & Ivie, 1935, which now includes one species endemic to the south-eastern USA and another from Argentinean Patagonia.